PENGARUH SOSIAL EKONOMI TERHADAP USIA PERKAWINAN PERTAMA PEREMPUAN DI KECAMATAN DENPASAR SELATAN - Made Heny Urmila Dewi, I Putu Govinda Madita Putra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
ABSTRACT The purpose of this study was to analyze socioeconomic interactions consisting of: education level, income level, employment status and living environment towards the age of the first marriage of women in South Denpasar District. The population in this study is the total number of married women in South Denpasar District with a total of 3,434 people. The sample in this study was calculated using the Slovin formula and obtained as many as 100 respondents. The data analysis technique used is multiple linear regression analysis. The analysis showed that the level of education (X1), income of parents (X2), employment status (X3) and neighborhood (X4) had a significant negative effect on the decision to make a first marriage of a woman in the South Denpasar District. This means that the higher the level of education and money that should be, also the more improving the status of work and living conditions, then young women will not discuss the problem of early marriage in the surrounding environment, so that it will be able to reduce the initial incidence of first marriage. Keywords: education level, agricultural income, employment status, living environment, age of first marriage of women